Our common arctic? A more sustainable EU-arctic nexus in light of the European green deal. Issue 2 (3rd July 2021) - Chuffart, Romain; Raspotnik, Andreas; Stępień, Adam
ABSTRACT: The European Union (EU) is a unique stakeholder in Arctic affairs. The EU is linked to the Arctic, affecting and affected by regional changes and developments, resulting in a multidimensional nexus of influences, impacts and overlapping agendas and stakeholders. As a global multi-level force and a major promoter of the concept of sustainable development the EU can also be a leader in setting standards for a more sustainable interaction between a major economy and the Arctic region. On the premise that the path towards a more comprehensive and integrated EU Arctic policy should focus on implementing more robust environmental policies in Europe, this paper argues that developing a distinct EU Arctic policy should only be regarded as secondary to building a – predominantly internal – regulatory framework that considers the ongoing changes in the Arctic. This article analyses the EU's capacity to be a global regulator and to set internal environmental standards with external influence on the Arctic. Specifically, this paper is concerned with the extent to which EU environmental policies and legislations can be regarded as contributing to the promotion of sustainable development in the Arctic with an analyses of the EU's energy-climate policy complex.